POMPA HIDRAM (POMPA AIR TANPA PENGGERAK ENERGI MEKANIK) - Anwar, Irwan; Wardianto, Dedi; Afdal, Afdal (ITP Press, 2023)
Hydram pump is the machine that conversion potential energy (PE = mgh) of water to kinetic energy (KE = ½ mv2) in intake pipe become water hammer in casing of hydram pump. That has capability to raised water from the pump with vertical elevation H2 = + 50 m to 500 m. It needs the minimal elevation + 1 m, the minimal debit 7 litres/minute and it depends on diameter and pump type. The principal of its construction has length of intake pipe L = 5 to 10 x H1 (vertical fall).